Pengaruh Green Banking,Capital Adequacy Ratio,dan Bopo Terhadap Profitabilitas Bank Umum Syariah Di Indonesia (2022-2024) - Naja Shakira (CV. ITTC INDONESIA, 2025)
This study aims to analyze the influence of Green Banking (GB), Capital Adequacy Ratio (CAR), and Biaya Operasional Pendapatan Operasional (BOPO) on the profitability of Islamic Commercial Banks in Indonesia during the 2022-2024 period. Employing a quantitative approach and associative research type, the study utilizes secondary data from annual reports of 7 selected Islamic banks, analyzed using STATA 15. The Common Effect Model was identified as the best model. Classical assumption tests indicated normally distributed residuals, no multicollinearity (VIFs < 10), and no heteroskedasticity (Prob > F = 0.5569). The F-test revealed that GB, CAR, and BOPO do not simultaneously influence profitability (Prob > F = 0.0918). However, the t-test showed that Green Banking partially affects profitability (P > |t| = 0.038), while CAR (P > |t| = 0.477) and BOPO (P > |t| = 0.059) do not. The R-squared value of 0.3085 indicates that 30.85% of profitability variation is explained by the independent variables.